Associations between prescribed benzodiazepines, overdose death and buprenorphine discontinuation among people receiving buprenorphine. (20th January 2020) - Park, Tae Woo; Larochelle, Marc R.; Saitz, Richard; Wang, Na; Bernson, Dana; Walley, Alexander Y.
ABSTRACT: Background and Aims: Benzodiazepines are commonly prescribed to patients with opioid use disorder receiving buprenorphine treatment, yet may increase overdose risk. However, prescribed benzodiazepines may improve retention in care by reducing buprenorphine discontinuation and thus may prevent relapse to illicit opioid use. We aimed to test the association between benzodiazepine prescription and fatal opioid overdose, non‐fatal opioid overdose, all‐cause mortality and buprenorphine discontinuation. Design and Setting: This was a retrospective cohort study using five individually linked data sets from Massachusetts, United States government agencies. Participants: We studied 63 389 Massachusetts residents aged 18 years or older who received buprenorphine treatment between January 2012 and December 2015. Measurements: Filled benzodiazepine prescription during buprenorphine treatment was the main independent variable. The primary outcome was time to fatal opioid overdose. Secondary outcomes were time to non‐fatal opioid overdose, all‐cause mortality and buprenorphine discontinuation. We defined buprenorphine discontinuation as having a 30‐day gap without another prescription following the end date of the previous prescription. We used Cox proportional hazards models to calculate hazards ratios that tested the association between receipt of benzodiazepines and all outcomes, restricted to periods during buprenorphine treatment. Findings: Of the 63 345 individuals who received buprenorphine, 24% filled at least one benzodiazepine prescription during buprenorphine treatment. Thirty‐one per cent of the 183 deaths from opioid overdose occurred when individuals received benzodiazepines during buprenorphine treatment. Benzodiazepine receipt during buprenorphine treatment was associated with an increased risk of fatal opioid overdose adjusted hazard ratio (HR) = 2.92, 95% confidence interval (CI) = 2.10‐4.06, non‐fatal opioid overdose, adjusted HR = 2.05, 95% CI, 1.68‐2.50, all‐cause mortality, adjusted HR = 1.90, 95% CI, 1.48‐2.44 and a decreased risk of buprenorphine discontinuation, adjusted HR = 0.87, 95% CI, 0.85‐0.89. Conclusions: Benzodiazepine receipt appears to be associated with both increased risk of opioid overdose and all‐cause mortality and decreased risk of buprenorphine discontinuation among people receiving buprenorphine.